Structural diversity in the solid-state architectures of bis(4-pyridyl)acetylene and its derivatives - Shotonwa, Ibukun Oluwaseun; Boere, Rene Theodoor (European Journal of Chemistry, 2020)
The crystals of bis(4-pyridyl)acetylene are orthorhombic and belong to the space group Fddd. Solid-state investigation using conventional and Hirshfeld analytical techniques revealed valuable data and structural diversities that explain the wide gap between established crystal reports of co-crystals and metal organic frameworks and the pure form of the title compound. Hirshfeld surface analysis in this wise has proved to be a useful tool in unravelling complex intermolecular interactions and simplifying them at the 2D and 3D levels using sub-tools such as fingerprint plots and electrostatic potential surfaces. Both techniques have shown that the H∙∙∙Npyr interactions in the title compound are shorter than those in its polymorphic counterpart by 0.2 Å. The more stable network provided by hetero-molecular interactions in co-crystals and metal complexes of bis(4-pyridyl)acetylene shed light on their lengthy existence compared to the less favorable homo-molecular interactions in pure molecules of bis(4-pyridyl)acetylene.